Determination of biologically active compounds in lipophilic extracts of pumpkin using thin layer chromatography - E. A. Degtyaryovа; V. A. Grudko; L. I. Vishnevskaya; E. I. Bisaga (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. Carotenoids are a common and important class of natural fat-soluble pigments. The prevention of free radicals formation is the carotenoid’s primary effect. One of the tasks while creating medicines which contain carotenoids is the identification of them in plant objects.